Evolutionary dynamics of polyadenylation signals and their recognition strategies in protists - Sajek, Marcin P.; Bilodeau, Danielle Y.; Beer, Michael A.; Horton, Emma; Miyamoto, Yukiko; Velle, Katrina B.; Eckmann, Lars; Fritz-Laylin, Lillian; Rissland, Olivia S.; Mukherjee, Neelanjan

(untitled) (Genome Research, 2024)
The poly(A) signal, together with auxiliary elements, directs cleavage of a pre-mRNA and thus determines the 3′ end of the mature transcript. In many species, including humans, the poly(A) signal is an AAUAAA hexamer, but we recently found that the deeply branching eukaryote Giardia lamblia uses a distinct hexamer (AGURAA) and lacks any known auxiliary elements. Our discovery prompted us to explore the evolutionary dynamics of poly(A) signals and auxiliary elements in the eukaryotic kingdom. We use direct RNA sequencing to determine poly(A) signals for four protists within the Metamonada clade (which also contains G. lamblia) and two outgroup protists. These experiments reveal that the AAUAAA hexamer serves as the poly(A) signal in at least four different eukaryotic clades, indicating that it is likely the ancestral signal, whereas the unusual Giardia version is derived. We find that the use and relative strengths of auxiliary elements are also plastic; in fact, within Metamonada, species like G. lamblia make use of a previously unrecognized auxiliary element where nucleotides flanking the poly(A) signal itself specify genuine cleavage sites. Thus, despite the fundamental nature of pre-mRNA cleavage for the expression of all protein-coding genes, the motifs controlling this process are dynamic on evolutionary timescales, providing motivation for future biochemical and structural studies as well as new therapeutic angles to target eukaryotic pathogens.